Fathers' Dosage in Community‐based Programs for Low‐income Fathers. Issue 1 (10th December 2018) - Fagan, Jay; Pearson, Jessica
Abstract : Community‐based programs for low‐income fathers often struggle to get fathers to attend services and activities. This paper reviews the literature examining approaches to measuring dosage in fatherhood programs, rates of dosage, influences on dosage, and the associations between dosage and fathers' outcomes. Studies were limited to programs that conducted randomized control trials, quasi‐experimental studies, and one‐group pretest/post‐test designs. Although most programs report low or moderate dosage levels, some programs achieve high levels of fathers' participation in parenting, coparenting, and economic security classes. Few studies examined dosage in relation to father outcomes. All but one of seven studies reporting effects showed that higher dose levels had positive associations with outcomes such as engagement with children, parenting satisfaction and self‐efficacy, perception of coparenting quality, payment of child support, and earnings from work. This paper discusses future directions for studying father's dosage in fatherhood programs. Resumen: En los programas comunitarios para padres de bajos recursos generalmente es difícil lograr que los padres asistan a los servicios y a las actividades que ofrecen. Este artículo revisa los métodos de análisis de las publicaciones para medir la cantidad de padres en los programas sobre paternidad, los índices de asistencia, las influencias en la asistencia y las asociaciones entre la asistencia y las respuestas de los padres. Los estudios se limitaron a los programas que llevaron a cabo ensayos controlados aleatorizados, estudios cuasiexperimentales y diseños de pruebas de entrada y pruebas de salida de un grupo. Aunque la mayoría de los programas informan niveles de asistencia bajos o moderados, algunos programas logran altos niveles de participación de los padres en las clases sobre crianza, cocrianza y seguridad económica de los niños. Pocos estudios analizaron la asistencia en relación con las respuestas de los padres. Todos excepto uno de siete estudios que informaron efectos indicaron que los niveles más altos de asistencia tuvieron asociaciones positivas con las respuestas de los padres, como compromiso con los niños, satisfacción con la crianza y autoeficacia, percepción de la calidad de la cocrianza, pago de la cuota alimentaria e ingresos de un trabajo. En este artículo se debaten las futuras direcciones para estudiar la asistencia de los padres en los programas sobre paternidad. 摘要: 针对低收入父亲的社区项目通常很难让这一类人群关注以他们为对象的服务和相关活动。本论文对相关研究文献进行了综述。这些研究调查了以父亲为服务对象的项目中父亲的剂量使用的测量方式, 以及对剂量率、剂量效应的测量, 还探究了父亲使用剂量与其收入之间的关联性。综述选取的研究在设计上限于以下几种:随机控制的试验, 类实验性研究, 和同一个测试组的前测和后测。尽管大多数项目报告显示了较低的或中等的使用剂量, 也有一些项目实现了父亲在培养教育孩子、共同抚育孩子、维护经济稳定课程等方面的较高参与水平, 但是很少有研究涉及剂量使用和父亲的收入状况的关系。在7个研究中除了1个研究之外, 其余均报告了较高的剂量水平与如下几个方面的效果有正相关:和孩子的互动, 做家长的满意度和自我效能感, 对和伴侣一起共同养育孩子的教育质量的认识, 孩子抚养费的支付, 和工作所得收入。本论文讨论了今后对父亲项目的研究中有关父亲的使用剂量方面的研究方向。